The trade-off between deepening and broadening of democracy: Lessons from youth enfranchisement - Anna Maria Koukal; Patricia Schafer; Reiner Eichenberger (Center for Research in Economics, Management and the Arts (CREMA), 2020)
Broadening democracy by lowering the voting age is on the political agenda in many democratic societies. Previous suffrage extensions suggest that there are systematic differences between what parliaments decide and what voters want with respect to enfranchisement of new groups. This paper analyzes a new municipality level dataset of two Swiss federal referendums on lowering the voting age from 20 to 18. We focus on the role of institutional price variations by (i) the depth of democracy proxied by the strength of direct democratic institutions and (ii) the size of the new electorate. Our results provide evidence that the price the current electorate faces - thus their potential influence loss - varies with the strength of direct democracy and affects citizens' willingness to lower the voting age. Moreover, we find systematic price reactions of present voters to the number of new voters.
Keywords: D72; D02; J15; P16; 330; voting age; youth enfranchisement; direct democracy; power loss